Method of treating catalyst

By hydrothermal treatment of nickel-containing catalysts, the problem of decreasing catalyst activity is solved, the selectivity and conversion rate are significantly improved, and the service life is extended.

CN119768232APending Publication Date: 2025-04-04EVONIK OXENO GMBH & CO KG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380060559.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-19
Filing Date
2023-06-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The activity of existing catalysts decreases during use, resulting in a decrease in conversion and selectivity, and the activity of fresh catalysts is not sufficient to ensure economicality.

Method used

The nickel-containing catalyst is treated by a hydrothermal treatment method, including heat treatment at a temperature of 500°C to 900°C, followed by impregnation with an aqueous solution or ammonia solution of a nickel-containing compound, hydrothermal treatment, and finally drying and calcining.

Benefits of technology

Through hydrothermal treatment, the selectivity and conversion of the catalyst are significantly improved, the service life of the catalyst is extended, and its mechanical properties are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005275992990000081
    Figure BDA0005275992990000081
  • Figure BDA0005275992990000082
    Figure BDA0005275992990000082
  • Figure BDA0005275992990000083
    Figure BDA0005275992990000083
Patent Text Reader

Abstract

The subject of the invention is a process for treating a catalyst wherein said process comprises a hydrothermal treatment step wherein the drying rate is less than the subsequent drying. The catalyst can be treated with the process according to the invention before its first use, preferably before use in oligomerization, or after its use, preferably after use in oligomerization.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for treating a catalyst, wherein the method comprises a hydrothermal treatment step, wherein the drying rate is less than the subsequent drying. The catalyst can be treated with the method of the invention before its first use, preferably before use in oligomerization, or after its use, preferably after use in oligomerization.

[0002] There are hardly any processes in industrial chemistry that do not use catalysts. Some of the catalysts used contain nickel as the active metal, for example in hydrogenation or oligomerization. In hydrogenation, unsaturated hydrocarbons are (partially) saturated by bonding hydrogen. In oligomerization, unsaturated hydrocarbons react with themselves to form correspondingly longer chain hydrocarbons, so-called oligomers (for example dimers, trimers or tetramers).

[0003] It is well known that catalysts lose their activity after a period of use in chemical processes. This means that important parameters such as conversion or selectivity become lower over time. However, freshly produced catalysts may also not be active enough for economic viability. Basic solutions to this problem are pretreatment of fresh catalysts or regeneration of catalysts with reduced activity. Corresponding methods have been published in the literature many times.

[0004] For industrial-scale processes, process improvement is a permanent goal. This includes the goal of improving the catalysts used and their activity so that the process can also be run more economically on an industrial scale.

[0005] The object of the present invention is therefore to provide a method for treating a catalyst, preferably an oligomerization catalyst, which method can improve the properties of the catalyst. In particular, when used for oligomerization, higher selectivities and higher conversions should be achieved without negatively affecting the service life and mechanical properties, such as strength, of the catalyst.

[0006] The object underlying the invention is achieved by a method for treating a catalyst according to claim 1. Preferred embodiments are given in the dependent claims.

[0007] Therefore, the method of the present invention is a method for treating a nickel-containing catalyst, wherein the method comprises at least the following steps:

[0008] a) heat treating the catalyst at a temperature of 500° C. to 900° C. to remove carbonaceous deposits;

[0009] b) impregnating the catalyst with an aqueous solution or an ammonia solution containing a nickel compound;

[0010] c) subjecting the catalyst to a hydrothermal treatment, wherein the hydrothermal treatment is carried out by heating the catalyst from room temperature to a temperature of 75° C. to 150° C., preferably 80° C. to 110° C. and optionally keeping it at this temperature until a residual moisture of maximum 30%, preferably maximum 50%, is obtained;

[0011] d) drying the catalyst, wherein the drying in step cd) has a higher drying rate than the hydrothermal treatment in step bc) and wherein the drying is carried out until a residual moisture of maximum 15%, preferably maximum 10%, is obtained; and

[0012] e) Calcination of the catalyst.

[0013] The composition of the oligomerization catalyst is: 15% to 50% by weight, preferably 15% to 40% by weight, of NiO, 10% to 30% by weight, 55% to 70% by weight, of SiO and 0.01% to 2.5% by weight, preferably 0.01% to 2.5% by weight, of alkali metal oxides, preferably sodium oxide. These data are based on a total composition of 100% by weight. In a particularly preferred embodiment of the invention, the oligomerization catalyst is substantially free of titanium dioxide and / or zirconium dioxide, in particular the oligomerization catalyst contains less than 0.5% by weight, preferably less than 0.1% by weight, particularly preferably less than 0.01% by weight of titanium dioxide and / or zirconium dioxide in its total composition.

[0014] According to the invention, the specific surface area of ​​the oligomerization catalyst (calculated according to BET) may be between 150 and 400 m 2 / g, preferably 190 to 350m 2 / g, particularly preferably 220 to 330m 2 / g. The BET surface area is measured by nitrogen physical adsorption according to DIN ISO 9277 (version: 2014-01).

[0015] In another preferred embodiment, the oligomerization catalyst comprises mesopores and macropores, i.e. has a bimodal pore size distribution. The mesopores of the oligomerization catalyst of the invention have an average pore size of 5 to 15 nm, preferably 7 to 14 nm, particularly preferably 9 to 13 nm. In contrast, the macropores of the oligomerization catalyst of the invention preferably have an average pore size of 1 to 100 μm, particularly preferably 2 to 50 μm. The average pore volume of the oligomerization catalyst of the invention, i.e. the average pore volume of the mesopores and the macropores, can be 0.5 to 1.5 cm 3 / g, preferably 0.7 to 1.3 cm 3 The average pore diameter and the average pore volume can be determined by mercury intrusion porosimetry in accordance with DIN 66133 (edition: 1993-06).

[0016] The oligomerization catalyst of the present invention is preferably present in the form of pellets. In addition, the average particle size (d50) of the oligomerization catalyst of the present invention can be 0.1 mm to 7 mm, preferably 0.5 to 6 mm, particularly preferably 1 mm to 5 mm. The average particle size can be determined by imaging methods, in particular by the methods cited in the standards ISO 13322-1 (version: 2004-12-01) and ISO 13322-2 (version: 2006-11-01). A suitable device for analyzing the particle size is, for example, the Camsizer 2006 (Retsch Technology).

[0017] In another preferred embodiment, the bulk compressive strength (BCS) of the oligomerization catalyst is greater than 0.5 MPa, preferably greater than 0.6 MPa, particularly preferably greater than 0.8 MPa. The BCS value is a measure of the mechanical strength of the mineral granules. The bulk compressive strength (BCS) of a solid is understood to be a parameter defined as the pressure in MPa, wherein when a solid sample is subjected to pressure through a piston in a tube, 0.5% by weight of fines (i.e. particles sieved out using a sieve with a mesh size of 0.425 mm) are formed. For this purpose, 20 ml of the solid is pre-screened with a sieve (mesh size: 0.425 mm), loaded into a cylindrical sample tube (inner diameter: 27.6 mm, wall thickness: 5 mm, height: 50 mm), and a 5 ml steel ball (diameter: 3.9 mm) is placed on the top surface of the solid. Subsequently, the solid is subjected to different (increasing) pressures within three minutes. The fines formed by the pressure are then separated by sieving, weighed as a total in each case and determined as a percentage. This process was continued until a fine fraction amount of 0.5 wt. % was reached.

[0018] The oligomerization catalyst can also be characterized by its maximum apparent density. In a preferred embodiment, the maximum apparent density of the oligomerization catalyst of the present invention is from 0.1 to 2 g / cm 3 , preferably 0.2 to 1.5 g / cm 3 , particularly preferably 0.3 to 1.0 g / cm 3 The apparent density can be determined using a measuring cylinder. A certain volume of the solid to be tested is placed in the measuring cylinder, for example using a suitable metering device such as DR100 (Retsch), and the measuring cylinder is then weighed. The maximum apparent density can be determined from the weight and volume. It is optionally necessary to subtract residual moisture from the sample weight.

[0019] The oligomerization catalyst of the present invention is made by a process comprising the steps generally described below:

[0020] 1) mixing an amorphous silica-alumina support material, an aluminum-containing and silicon-free binder and at least a portion of a nickel source and optionally also an alkali source, and granulating the mixture obtained therefrom;

[0021] 2) applying (impregnating) at least a portion of the nickel source and / or alkali source to the granules produced in step a), provided that the entire nickel source and / or alkali source has not already been mixed with the silica-alumina support material and the aluminum-containing, silicon-free binder in step a); and

[0022] c) calcining the pellets to prepare an oligomerization catalyst.

[0023] Corresponding methods and the precise conditions are known and are disclosed, for example, in EP 3549669 A1, EP 3546065 A1 or EP 3542898 A1.

[0024] After the catalyst has been prepared, it can be used for the oligomerization of olefins. However, the catalyst can also be subjected to the process of the invention after its preparation but before its first use, wherein although some preparation steps are repeated, an additional hydrothermal step is also performed. The direct preparation of the catalyst with a hydrothermal treatment step is not part of the present invention.

[0025] The process according to the invention can also be used to regenerate a catalyst which has already been used for oligomerization. With increasing usage time of the oligomerization catalyst in the oligomerization, a decrease in conversion and / or selectivity may occur, for example due to deposits of organic compounds. The catalyst according to the invention can be regenerated by the process according to the invention after use in the oligomerization reaction, i.e. with an improved oligomerization activity compared to the previous state.

[0026] The individual steps should be explained in more detail below:

[0027] Step a)

[0028] After it is used for oligomerization, the oligomerization catalyst may have deposits of organic substances. It is generally recommended to remove these deposits. Preferably, at least a portion of the organic compounds deposited in the catalyst are removed by heat treatment (oxidation) in step a) to thereby form carbon oxides and water. Step a) can be carried out continuously or discontinuously in a furnace, for example in a rotary kiln or a shaft furnace. For this purpose, the oligomerization catalyst is supplied to the furnace and is preferably maintained at a predetermined furnace temperature of 500° C. to 900° C., particularly preferably 600° C. to 850° C. Combustion air is generally used in step a). The combustion air used is preferably supplied in a countercurrent manner, and more air is optionally blown into the pellets (oligomerization catalyst) through a suitable inlet to ensure faster oxidation.

[0029] Step b)

[0030] In step b), the catalyst obtained from step a) is impregnated with an aqueous or ammonia solution. In the context of the present invention, impregnation means contacting the catalyst with an aqueous or ammonia solution, which can be done, for example, by spraying until a permanent film of liquid appears on the surface (incipient wetness). By impregnation, at least the water required for the subsequent hydrothermal treatment is introduced.

[0031] According to the invention, the aqueous solution or ammonia solution preferably contains a nickel compound. This allows an additional amount of nickel to be deposited on the oligomerization catalyst. In principle, various soluble nickel compounds, such as nickel nitrate (Ni(NO3)2), nickel acetate (Ni(ac)2), nickel acetylacetonate (Ni(acac)2), nickel sulfate (NiSO4) or nickel carbonate (NiCO3) can be used for this purpose to prepare the aqueous solution or ammonia solution of nickel.

[0032] The use of NiHAC solutions, i.e. Ni(CO3) ammonia solutions, has proven to be particularly advantageous. The nickel content of such solutions used can be from 0.5% to 14% by weight, in particular from 2% to 10% by weight, very particularly from 4% to 8% by weight.

[0033] Step c)

[0034] After the impregnation, a hydrothermal treatment is carried out in step c). The hydrothermal treatment is carried out by heating the catalyst from room temperature to a temperature of 75° C. to 150° C., preferably 80° C. to 110° C., and optionally keeping it at this temperature until a residual moisture of maximum 30%, preferably maximum 50%, is obtained. The term "residual moisture" is based on the state of the catalyst before the hydrothermal treatment, in which the catalyst has a residual moisture of 100%. The catalyst is therefore not dried at all or only dried slowly by the hydrothermal treatment.

[0035] Hydrothermal treatment is the core of the present method and can be clearly distinguished from the subsequent drying in step d). In the hydrothermal treatment, the drying rate (mass loss of evaporable components (such as water or ammonia) per unit time (such as minutes)) is significantly lower than the drying in step d). The hydrothermal treatment in step c) can be carried out at normal pressure or a pressure higher than normal pressure, but not under vacuum. The hydrothermal treatment is preferably carried out in a device suitable for this and in which the drying rate can be limited. The hydrothermal treatment in step c) can also be carried out in a closed container, for example, so that the drying rate based on the container volume is equal to 0. If the hydrothermal treatment is carried out in a closed container, the pressure will increase due to the evaporated water and evaporated ammonia. For safety reasons, in this case, the closed container may need to have a pressure relief valve to prevent the pressure from becoming too high.

[0036] Step d)

[0037] Subsequently, the oligomerization catalyst is dried in a suitable drying device, such as a belt dryer with air flow, or a conical dryer, at a temperature of 80° C. to 250° C., preferably 100° C. to 220° C., and normal pressure or vacuum. The drying rate of the drying in step d) is higher than the hydrothermal treatment in step c). In a preferred embodiment, the drying device and the device for the hydrothermal treatment are not the same. Instead, the oligomerization catalyst that is not completely dried can be taken out of the device for carrying out step c) and loaded into the drying device.

[0038] Step e)

[0039] Step e) is the final calcination. The calcination of the oligomerization catalyst can be carried out continuously or discontinuously in a suitable furnace, such as a shaft furnace or a rotary furnace. In the case of continuous calcination, it is further preferred to conduct the gas countercurrent over the oligomerization catalyst (pellets). The gas used can be air, nitrogen or a mixture thereof. The gas flow can be 0.2 to 4 m / s per kg of pellets per hour. 3 The inlet temperature of the gas can be 400° C. to 900° C., preferably 450° C. to 750° C. In addition to the heat introduced by the gas, energy can also be introduced by active heating of the furnace walls.

[0040] The calcination temperature in the furnace can be 400° C. to 900° C., preferably 450° C. to 850° C. This temperature can be maintained for several hours, preferably 0.5 to 20 hours, particularly preferably 1 to 10 hours, before the pellets are cooled. Cooling is preferably carried out in an air stream.

[0041] The oligomerization catalyst of the invention or the catalyst prepared or regenerated by the process of the invention is particularly useful for the oligomerization of C3- to C6-olefins, preferably C3- to C5-olefins, particularly preferably C4-olefins or olefin-containing input mixtures based thereon. The olefins or olefin-containing input mixtures are used as reactant streams.

[0042] After carrying out the process according to the invention, the catalyst can be used for the oligomerization of olefins. Therefore, another subject of the present invention is also a process for the oligomerization of C3- to C6-olefins, wherein an olefin-containing input mixture containing C3- to C6-olefins is passed in at least one reaction zone over a catalyst, wherein the catalyst has been treated according to the process according to the invention.

[0043] The olefin used in the process of the present invention is C3- to C6-olefin, preferably C3- to C5-olefin, particularly preferably C4-olefin or an olefin-containing input mixture based thereon, which mixture may also contain a certain proportion of similar alkanes. Suitable olefins are especially α-olefins, normal olefins and cycloolefins. The olefin used as a reactant is preferably a normal olefin. In a particularly preferred embodiment, the olefin is n-butene. According to the present invention, the term "olefin-containing input mixture based thereon" should be understood as referring to various types of mixtures of the corresponding C3- to C6-olefins to be oligomerized that are capable of being oligomerized in an amount. The olefin-containing input mixture preferably contains almost no other unsaturated compounds and polyunsaturated compounds, such as dienes or acetylene derivatives. It is preferred to use an olefin-containing input mixture containing (based on the olefin ratio) less than 5% by weight, particularly less than 2% by weight of branched olefins. It is also preferred to use an olefin-containing input mixture containing less than 2% by weight of branched olefins (particularly isoolefins).

[0044] Propylene (C3) is produced on an industrial scale by cracking naphtha and is a basic chemical that is easily accessible. C5-olefins are contained in the light gasoline fraction from a refinery or cracker. Industrial mixtures containing linear C4-olefins are light gasoline fractions from refineries, C4 fractions from FC crackers or steam crackers, mixtures from Fischer-Tropsch synthesis, mixtures from butane dehydrogenation, and mixtures formed by metathesis or other industrial processes. A linear butene mixture suitable for the method of the present invention can be obtained, for example, from the C4- fraction of a steam cracker. Butadiene is removed in the first step. This is achieved by extracting or extractive distilling butadiene or by its selective hydrogenation. In both cases, a C4- fraction that is almost free of butadiene, i.e., raffinate I, is obtained. In the second step, isobutylene is removed from the C4- stream, for example, by reacting with methanol to prepare methyl tert-butyl ether (MTBE). Other possibilities are to react isobutylene from raffinate I with water to generate tert-butyl alcohol, or to carry out acid-catalyzed oligomerization of isobutylene to generate diisobutylene. If desired, the now isobutene-free C4-fraction, ie the raffinate II, comprises linear butenes and optionally butanes. Optionally, 1-butene can still be separated off by distillation. Both fractions (the fraction comprising but-1-ene or the fraction comprising but-2-ene) can be used in the process according to the invention.

[0045] In a further preferred embodiment, a C4-olefin-containing substance stream is supplied to the process as an olefin-containing input mixture. Suitable olefin-containing input mixtures for this purpose are in particular raffinate I (butadiene-free C4-fraction from a steam cracker) and raffinate II (butadiene-free and isobutene-free C4-fraction from a steam cracker).

[0046] Another possibility for preparing a suitable olefin-containing feed mixture is to hydroisomerize raffinate I, raffinate II or a hydrocarbon mixture of similar composition in a reaction column. In particular, mixtures consisting of 2-butene, a small proportion of 1-butene and optionally n-butane and also isobutane and isobutene can be obtained here.

[0047] The oligomerization reaction is usually carried out at a temperature of 50° C. to 200° C., preferably 60° C. to 180° C., preferably 60° C. to 130° C. and a pressure of 10 to 70 bar, preferably 20 to 55 bar. If the oligomerization is to be carried out in the liquid phase, the pressure and temperature parameters must be selected so that the reactant stream (olefin or olefin-containing input mixture used) is in the liquid phase. The weight-based space velocity (mass of reactant per unit mass of catalyst per unit time; weight hourly space velocity (WHSV) of the olefin-containing input mixture) is 1 g of reactant per g of catalyst per hour (=1 h -1 ) to 190h -1 , preferably 2h -1 Up to 35h -1 , especially preferably 3h -1 Up to 25 -1 However, typical conditions are also known to those skilled in the art.

[0048] The oligomers prepared according to the method of the invention can be used in particular for the preparation of aldehydes, alcohols and carboxylic acids. Thus, for example, dimers of linear butenes provide nonanal mixtures by hydroformylation. This provides the corresponding carboxylic acids by oxidation or C9-alcohol mixtures by hydrogenation. C9-acid mixtures can be used for the preparation of lubricants or driers. C9-alcohol mixtures are precursors for the preparation of plasticizers, in particular diisononyl phthalate, diisononyl terephthalate, cyclohexane-1,4-dicarboxylic acid diisononyl ester or cyclohexane-1,2-dicarboxylic acid diisononyl ester.

[0049] The invention is explained in more detail below with the aid of examples.Alternative embodiments of the invention can be obtained analogously. Example:

[0050] Original catalyst material

[0051] The catalyst material is derived from a butene oligomerization production plant and has a typical composition of about 20% by weight of NiO on Al2O3 / SiO2. The used catalyst material is first regenerated so that the catalyst material is heat treated at a temperature of 550°C to 650°C in a rotary furnace in the first step, post-impregnated with a 5% Ni solution in the second step, and dried for more than 10 hours at about 110°C to 120°C in a drying oven in the subsequent step until the residual moisture is about 15%, and then calcined at 650°C in a tube furnace. Comparative catalyst 2 was not subjected to additional hydrothermal treatment. In order to prepare the catalyst 1 of the present invention, a hydrothermal treatment was also carried out before drying in a drying oven. Here, the material was hydrothermally treated for 6 hours at 110°C in a drying oven in a container that was only partially open (sealed with a venting nut with a PTFE membrane) until the residual moisture was about 30%, wherein the drying rate in the subsequent drying was higher. The two catalysts prepared in this way were used for catalytic testing as follows.

[0052] Approximately 350 g of catalyst were introduced into a metal tube with an internal diameter of 21 mm in each case. Glass beads with a diameter of 2 mm were added before and after the catalyst, which served as preheating and cooling stages. The oligomerization was carried out at 30 bar and a loading of 2 g / h of butene per gram of catalyst using a feed stream, wherein the reaction temperature was varied between 80° C. and 100° C. The product was analyzed by gas chromatography for butene conversion and octene linearity. The composition of the feed stream used for the oligomerization is shown in Table 1 below.

[0053] Table 1: Composition of feed streams

[0054]

[0055] Table 2 shows the conversions achieved for the feed streams of catalyst 1 (according to the invention) and catalyst 2 (not according to the invention) as a function of the temperature and the ISO index derived therefrom.

[0056] The linearity of the oligomerization products or the dimers formed is described by the ISO index and represents the average number of methyl branches in the dimer. For example (for butene as reactant) n-octene contributes 0 to the ISO index of the C8-fraction, methylheptene 1 and dimethylhexenes 2. The lower the ISO index, the more linear the structure of the molecules in the respective fraction.

[0057] The ISO index is calculated using the following general formula:

[0058]

[0059] Thus, a dimer mixture with an ISO index of 1.0 has on average exactly one methyl branch per dimer molecule.The ratio of the individual isomers can be determined, for example, by gas chromatography.

[0060] Table 2: Catalyst results

[0061]

[0062] This shows that the inventive catalyst 1 sometimes achieves significantly higher conversions at similar or lower ISO indices. This is surprising, since higher conversions are usually accompanied by lower linearity of the oligomers in the product mixture. Thus, the additional hydrothermal treatment ensures an increased effectiveness of the catalyst independently of the temperature.

Claims

1. A method for treating a nickel-containing catalyst, wherein the method comprises at least the following steps: a) heat treating the catalyst at a temperature of 500° C. to 900° C. to remove carbonaceous deposits; b) impregnating the catalyst with an aqueous solution or an ammonia solution containing a nickel compound; c) subjecting the catalyst to a hydrothermal treatment, wherein the hydrothermal treatment is carried out by heating the catalyst from room temperature to a temperature of 75° C. to 150° C., preferably 80° C. to 110° C. and optionally keeping it at this temperature until a residual moisture of maximum 30%, preferably maximum 50%, is obtained; d) drying the catalyst, wherein the drying in step d) has a higher drying rate than the hydrothermal treatment in step c), and wherein the drying is carried out until a residual moisture of maximum 15%, preferably maximum 10%, is obtained; and e) Calcination of the catalyst.

2. The method according to claim 1, wherein the treatment is carried out after the catalyst is produced or for regeneration after use in a heterogeneous catalytic reaction, preferably oligomerization.

3. The method according to claim 1, wherein the nickel compound is selected from nickel nitrate (Ni(NO3)2), nickel acetate (Ni(ac)2), nickel acetylacetonate (Ni(acac)2), nickel sulfate (NiSO4), nickel citrate or nickel carbonate (NiCO3).

4. The method according to claim 4, wherein the aqueous solution or ammonia solution used is Ni(CO3) ammonia solution.

5. The method according to any one of the preceding claims, wherein the heat treatment in step a) is carried out at a temperature of 600 to 850°C.

6. The method according to any one of the preceding claims, wherein the duration of the hydrothermal treatment in step c) is from 1 to 24 hours.

7. The process according to any one of the preceding claims, wherein the drying in step d) is carried out at a temperature of 80 to 250°C, preferably 100 to 220°C.

8. The process according to any one of the preceding claims, wherein the drying in step d) is carried out such that the resulting dried material has a loss on drying (LOD) of maximum 5 wt.-% at 110°C.

9. The method according to any one of the preceding claims, wherein the drying rate in step d) is twice as high as in step c).

10. The method according to any one of the preceding claims, wherein the calcination in step e) is carried out at a temperature of 400 to 900°C, preferably 450 to 850°C.

11. The method according to any one of the preceding claims, wherein the calcination in step e) is carried out in an air flow, a nitrogen flow or a combination thereof.

12. The process according to any one of the preceding claims, wherein the catalyst has the following composition: 15 to 50 wt. % NiO, 10 to 30 wt. % Al2O3, 55 to 70 wt. % SiO2 and 0.01 to 2.5 wt. % alkali metal oxides.

13. A process according to any one of the preceding claims, wherein the catalyst has a nitrogen physisorption capacity of 150 to 400 m 2 / g BET specific surface area.

14. Process for the oligomerization of C3- to C6-olefins, wherein an olefin-containing input mixture containing C3- to C6-olefins is passed over a catalyst in at least one reaction zone, wherein the catalyst has been treated according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Method for producing an oligomerisation catalyst

    EP3542898A1

  • Oligomerisation catalyst based on nickel oxide and method for the oligomerisation of olefins

    EP3546065A1

  • Oligomerisation catalyst based on nickel oxide and method for c3-c6 olefin oligomerization using it

    EP3549669A1